Key concepts in radio studies - Chignell, Hugh.; Sage eBooks (London : SAGE, 2009)
'Key Concepts in Radio Studies' provides a comprehensive easy-to-use introduction to the field.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Radio; Radio broadcasting; Electronic books